Identification Of Low Public Interest in The Use Of Pedant Bridge Using Fault Tree Analysis Method In Batam City - Rafa Okta Fiana; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2023)
The bridge is construction to continue the road from lower obstacles such as ordinary traffic. Bridges also serve as a link between separate places. Crossing is a process or act of crossing from one place to another by crossing a specific activity. A crossing bridge is a facility intended for pedestrians to carry out crossing activities at crossing points on roads with heavy traffic conditions. The pedestrian bridge serves as a safe way for pedestrians. The crossing bridge also functions as a means of moving pedestrians who will cross. The city of Batam is one of the cities with quite severe traffic jams. Because this often happens when there are many access roads in the city of Batam, road widening is carried out. FTA can assist in recognizing the interrelationships between causes in a system and in evaluating the potential impact of causes in the event of a system failure. The FTA procedure is based on creating a visual representation that identifies each potential cause, the relationship between the causes, and the prioritized prevention strategy.